Protective Effects and Mechanism of Radix Polygalae Against Neurological Diseases as Well as Effective Substance - Jiang, Ning; Wei, Shanshan; Zhang, Yiwen; He, Wenlu; Pei, Haiyue; Huang, Hong; Wang, Qiong; Liu, Xinmin (Frontiers in Psychiatry, 2021)
Radix Polygalae (also known as Yuanzhi), the dried rhizome of Polygala tenuifolia Willd, is a famous Chinese herb that has been widely used for centuries in traditional medicines including expectorants, tonics, tranquillizers and antipsychotic. This article reviews the neuroprotective effects of Radix Polygalae in preclinical models of central nervous system (CNS) disorders, especially anxiety, depression, declining cognition, Alzheimer's disease (AD) and Parkinson's disease (PD). Radix Polygalae chemical composition as well as the the underlying mechanisms of action were also reviewed. We found that Radix Polygalae possesses a broad range of beneficial effects against the above mentioned conditions. The mechanisms of action is multifold and include several properties such as antioxidant and associated apoptotic effects; anti-inflammatory and associated apoptotic effects; neurogenesis, regeneration, differentiation and neuronal plasticity improvement; Hypothalamic–pituitary–adrenal axis (HPA) regulation; neurotransmitter release and receptor activation (A2AR, NMDA-R, GluR, and AMPA-R). Nevertheless, the detailed mechanisms underlying this array of pharmacological effects observed in vitro and in vivo still needs further investigation to attain a coherent neuroprotective profile.